Revitalizing Teacher Leadership in Secondary Schools Through a Values and Culture Approach: Towards Schools with a Collaborative and Adaptive Culture - Hidayah Yanti (Al-Qalam Institue, 2026)
Educational transformation in the era of digital disruption requires schools to build collaborative and adaptive cultures, which strongly depend on the quality of teacher leadership as instructional and learning leaders. However, many secondary schools still demonstrate weak teacher leadership due to hierarchical cultures and administrative, top-down approaches that restrict creativity and professional autonomy. This study aims to analyze the revitalization of teacher leadership based on school values and culture as a strategy for establishing a collaborative and adaptive learning ecosystem. The research employed a Systematic Literature Review (SLR) through structured searches of national and international scientific sources, followed by rigorous screening based on relevance criteria and thematic analysis to identify patterns and formulate conceptual synthesis. The findings indicate that professional values (trust, responsibility, collaboration, and innovation) and school culture serve as strategic foundations for strengthening teacher leadership, distributed leadership, and school transformation. The implications highlight the importance of teacher empowerment, participatory organizational restructuring, and the development of collective learning culture. In conclusion, revitalizing teacher leadership grounded in values and culture is essential for sustainable school transformation, and further empirical research is required to validate and operationalize its implementation in diverse secondary school contexts.